PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN PROSES DAN HASIL BELAJAR MATEMATIKA BAGI PESERTA DIDIK - syamsimar - syamsimar (LP3M STKIP Muhammadiyah Muara Bungo, 2021)
The problem in this research is the low process and learning outcomes of students in grade V in elementary school 94/II Muara Bungo this is evidenced by the results of the observation that the learning activities of students are still limited, especially in mathematics learning. This study aims to improve students’ mathematics learning processes and outcomes eith Problem Based Learning models on fractional material. This type of research is classroom action research. Classroom action research is carried out consisting of two research cycle with stages in each cycle including planning, implementing, observing, and reflecting. The applcation of the Problem Based Learning model process and the learning outcomes of grade V mathematics increased as expected. The improvement of the learning process that is evidenced from the results of teacher and student observation sheets. The results of teacher observation in cycle I is 60% and cycle II is 85%, the observation results of students in cycle I are 55% and cycle II is 80%. With the increase in the learning process also increases the learning outcomes of studens’ mathematics that is there are 5 students who have reached very good criteria if a percentage of 20% and 16 students who reach good criteria if a percentage of 64%.